Back Cover: Bioresponsive nanoplatforms for imaging and therapy of cardiovascular diseases (View 1/2022). Issue 1 (31st January 2022) - Li, Chenwen; Wu, Peng; Dou, Yin; Li, Qi; Zhang, Jianxiang
Abstract : Cardiovascular diseases (CVDs), including myocardial infarction, atherosclerosis, restenosis, thrombosis, heart failure, aortic aneurysms, etc., are still the leading cause of death worldwide. In article number 20200137, Jianxiang Zhang and co‐workers have summarized recent advances in different nanoplatforms responsive to biochemical stimuli, such as pH, reactive oxygen species, and enzymes, with especial focus on their applications in imaging and therapy of typical CVDs.